Aetiology and outcome of pleural empyema in children admitted to Pietersburg Hospital Limpopo, South Africa - Tshamiswe, Mbilaelo (My University, 2022)
Introduction: Pleural empyema in children is associated with high morbidity and high mortality. Staphylococcus aureus has been shown to be the most common causative organism in developing countries. Study design: This study applied a retrospective quantitative descriptive study design. Study population: The population of the study is comprised of children (between 1 years and 13 years) admitted to Pietersburg Provincial Hospital with pleural empyema from January 2016 until December 2020. Objectives: The study aimed to determine the causative organisms of pleural empyema, the treatment outcomes, and the relationship between pleural empyema, TB, and HIV infection. Data collection: The National Health Laboratory Services database was used to identify patients who had pleural empyema. A self-generated data collection tool was used to obtain secondary data related to all patients who met the operational definition of pleural empyema during the defined time period. Results: Eleven participants met inclusion criteria. The mean age of participants was 42 months with 43.8 standard deviation and 64% were males and females were 36% . Of these participants, 40% cultured S. Aureus in the pleural fluid, 10% Streptococcus pneumoniae, 30% were sterile and 20% cultured other organisms such as Klebsiella pneumoniae and Haemophilus influenzae. Cloxacillin was the most prescribed antibiotic. Intercostal drainage was inserted in 91% of the participants of which 18% were successful, no further surgical intervention needed,73% had thoracotomy and VATS was offered to 91% of participants and it was followed by thoracotomy. Fibrinolytics were not offered to the participants in this study. The majority of patients, 55%, were discharged back to their peripheral hospitals and 27% of them died. PCV immunisation status of the children was not documented hence the relationship between pleural empyema and PCV immunisation could not be established. There was a positive correlation between age of patients with pleural empyema and ICU length of stay (r=89%; p=0,01) while another strong correlation was depicted between HIV status and hospital length of stay (r=88%, p=0,019). Results further show a positive association between outcome and surgery intervention offered (Chi=7,00; p=0,02). Conclusion: Our study showed that S. aureus is the leading cause of pleural empyema, with a predominance of thoracocentesis and thoracotomy offered as surgical interventions.
Thesis (M.Med. (Paediatrics and Child Health)) -- University of Limpopo, 2022
Keywords: Pleural empyema; Causative organisms; Treatment outcomes; Children; Empyema; Staphylococcus aureus; Children -- Mortality; Diseases -- Reporting; Children -- Diseases; Diseases -- Causes and theories of causation